Hysterosalpingography (HSG) Findings in Primary Infertility: Serial Cases - Lumbangaol, Anugerah Isabela; Dewi, Putu Utami; Sudiatmika, Dewa Gde Mahiswara (Universitas Muhammadiyah Surabaya, 2025)
Infertility is a condition in which a couple fails to achieve pregnancy after 12 months of unprotected sex. In Indonesia, the prevalence of infertility is estimated to be around 10-15%. Primary infertility occurs when a woman has never had a pregnancy. Hysterosalpingography (HSG) examination is a radiological modality that is often used to evaluate the condition of the uterus and fallopian tubes in infertile women. The case series features data from five female patients diagnosed with primary infertility, where each patient underwent an HSG examination, and the results of the analysis were based on radiological findings that included structural abnormalities in the uterus and fallopian tubes. The HSG findings showed various abnormalities such as hydrosalpinx, tubal occlusion, uterine arcuatus, uterine bicornuate, and salpingitis isthmica nodosa. Uterus arcuatus was found in two cases, while hydrosalpinx was detected in three cases. In addition, two cases showed the presence of bilateral occlusion of the fallopian tubes, which correlated with primary infertility. HSG examination is an effective modality for detecting various abnormalities in the female reproductive tract that contribute to primary infertility. Findings such as hydrosalpinx, tubal occlusion, and uterine anomalies play an important role in determining the right treatment strategy for patients.